Phase Diagram of BiFeO3/LaFeO3 Superlattices: Antiferroelectric‐Like State Stability Arising from Strain Effects and Symmetry Mismatch at Heterointerfaces. Issue 11 (27th March 2017) - Carcan, Benjamin; Bouyanfif, Houssny; El Marssi, Mimoun; Le Marrec, Françoise; Dupont, Loic; Davoisne, Carine; Wolfman, Jérôme; Arnold, Donna C.
Abstract : (BiFeO3 )(1− x )Λ /(LaFeO3 ) x Λ superlattices (SLs) have been grown using pulsed laser deposition and studied by X‐ray diffraction, transmission electron microscopy (TEM), and Raman spectroscopy. The composition is varied, 0.30 ≤ x ≤ 0.85, while the modulation period Λ is kept constant at about 10 nm. Unit cell doubling signatures typical of orthorhombic Pnma symmetry for x = 0.80 and 0.85 SLs and ¼{011} antiferroelectric PbZrO3 ‐like reflections in SLs with 0.30 ≤ x ≤ 0.7 are detected by TEM showing a complex structural mixture at the nanoscale level. The Raman spectra confirm these observations and show a change in the SLs from a Pnma LaFeO3 ‐like spectra for LaFeO3 ‐rich period to a PbZrO3 ‐like spectra for BiFeO3 ‐rich period. Electron–phonon interactions and resonant‐like excitations are also observed in the SLs. A temperature‐dependent X‐ray diffraction investigation shows a large shift of the paraelectric‐antiferroelectric phase transition scaling with the BiFeO3 thickness. This shift is correlated with the strain state and can be explained by a strong interplay between octahedral rotation/tilt and antipolar Bi displacement. Thickness–temperature phase diagram is constructed and differs from previous report showing the extreme sensitivity of the BiFeO3 phase stability to strain effects and rotation/tilt degrees of freedom. Abstract : Superlattices are ideal platforms to investigate competing orders that take place in many functional complex oxides. BiFeO3 /LaFeO3 superlattices are investigated and emergent antiferroelecric‐like ordering is revealed by complementary techniques. Phase diagram is proposed and BiFeO3 phase stability with thickness and temperature is highlighted.